Typy zaburzeń językowych w zespole Aspergera - Marta Korendo (Annales Universitatis Paedagogicae Cracoviensis. Studia Linguistica, 2023)
For many years, both the DSM‑IV and ICD-10 have built up the misconception that there are no language disorders in Asperger’s syndrome. This has had a significant impact on the problems with the diagnosis of Asperger syndrome, and has been the cause of many misdiagnoses. The current editions: DSM-5 and ICD-11 have not changed the established approach. Many years of research and clinical experience have allowed the author of this article to verify the view of normal speech and communication development in Asperger syndrome. We now know that children with ZA may manifest different types of disorders, concerning both systemic and communicative competence. The author of the article characterises the types of language problems observed in ZA, including: the specificity of early speech development, alalia (delayed speech development), aphasia, comprehension of speech and intonation of speech and indicates their sources and examples. This is of great importance in the context of the correct diagnosis and therapy of children on the autism spectrum, including the differential diagnosis of autism and Asperger syndrome.